Music in the baroque era from Monteverdi to Bach - Bukofzer, Manfred F. 1910-1955 (New York, N.Y. W. W. Norton & Company, Inc., 1947)
This history of the music of the Baroque Era in Europe--roughly, from the 17th century through the first half of the 18th--covers the entire field, from Monteverdi and Schütz at its inception to the great works of Bach and Handel.--Adapted from publisher description.
Chapter 1 : Renaissance versus Baroque music. Disintegration of stylistic unity ; Stylistic comparison between Renaissance and Baroque music ; The phases of Baroque music -- Chapter 2 : Early Baroque in Italy. The beginnings of the concerto style : Gabrieli ; The monody : Peri and Caccini ; Transformation of the madrigal : Monteverdi ; The influence of the dance on vocal music ; Emancipation of instrumental music : Frescobaldi ; The rise of the opera : Monteverdi ; Tradition and progress in sacred music -- Chapter 3 : Early and middle Baroque in the northern countries. The Netherlands school and its English background ; English antecedents : the abstract instrumental style ; The Netherlands: Sweelinck ; Germany and Austria in the 17th century ; Chorale and devotional song ; Chorale motet and choral concertato : Schein ; The dramatic concertato : Schütz ; Continuo Lied, opera and oratorio ; Instrumental music : Scheidt, Froberger, and Biber -- Chapter 4 : Italian music of the middle Baroque. The bel-canto style ; The chamber cantata : Luigi Rossi and Carissimi ; The oratorio : Carissimi and Stradella ; The Venetian opera school ; Instrumental music : the Bologna school -- Chapter 5 : French music under absolutism. The ballet de cour ; French reactions to Italian opera ; Comédie-ballet and the tragédie lyrique : Lully ; Cantata, oratorio, and church music ; Lute miniatures and keyboard music : Gaultier and Chambonnières ; Music in the Iberian peninsula, New Spain, and Colonial America -- Chapter 6 : English music during the commonwealth and restoration. The masque and the English opera : Lawes and Blow ; Consort music : Jenkins and Simpson ; Anglican church music : Porter, Humfrey, and Blow ; Henry Purcell, the Restoration genius -- Chapter 7 : Late Baroque : luxuriant counterpoint and concerto style. The culmination of late Baroque music in Italy ; The rise of tonality ; Concerto grosso and solo concerto ; Ensemble sonata and solo sonata ; Opera seria and opera buffa : cantata and sacred music ; Late Baroque and Rococo style in France ; Ensemble and clavecin music ; Opera and cantata in France -- Chapter 8 : Fusion of national styles : Bach. The state of instrumental music in Germany before Bach ; The state of protestant church music before Bach ; Bach : the early period ; Bach the organist : Weimar ; Bach the mentor : Cöthen ; Bach the cantor : Lepzig ; Bach, the past master -- Chapter 9 : Coordination of national styles : Handel. The state of secular vocal music in Germany before Handel ; Handel : German apprentice period ; Italian journeyman period ; English master period : operas, oratorios, instrumental music ; Bach and Handel, a comparison -- Chapter 10 : Form in Baroque music. Formal principles and formal schemes ; Style and form ; Audible and inaudible order -- Chapter 11 : Musical thought of the Baroque era. Code of performance : composer and performer ; Theory and practice of composition ; Musical speculation -- Chapter 12 : Sociology of Baroque music. Courtly musical institutions of state and church : private patronage ; Civic musical institutions : collective patronage ; Social and economic aspects of music and musicians.
Includes bibliographical references (pages 417-469) and index.
Keywords: Music -- 17th century -- History and criticism; Music -- 18th century -- History and criticism